Journal of Business Strategy, Finance and Management 2021
DOI: 10.12944/jbsfm.03.01-02.11
|View full text |Cite
|
Sign up to set email alerts
|

Omani Higher Education Students Attitude Towards Work During Study

Abstract: The work during study is widespread matter worldwide and in the Sultanate of Oman as well. Many Omani students are noticed work during their study. The aim of this research is to analyze the attitude of higher education Omani students towards working during study via identifying benefits they obtain and challenges they face. The quantitative research methodology was implemented via survey approach using structured questionnaire technique. The questionnaire was prepared and distributed to 220 higher education s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…While soft skill improvement has been identified as the primary benefit of parttime employment for students, social challenges have been noted as the most significant challenge they face (Al Habsi & Madbouly, 2021). Contrary to popular belief, studies have found that working while in school can have drawbacks.…”
Section: Perks and Setbacks Of A Working Studentmentioning
confidence: 99%
See 1 more Smart Citation
“…While soft skill improvement has been identified as the primary benefit of parttime employment for students, social challenges have been noted as the most significant challenge they face (Al Habsi & Madbouly, 2021). Contrary to popular belief, studies have found that working while in school can have drawbacks.…”
Section: Perks and Setbacks Of A Working Studentmentioning
confidence: 99%
“…Due to the restricted time available to students, time spent working may be at the expense of academic, social, recreational, and extra-curricular activities. Al Habsi and Madbouly (2021) highlight that working students often encounter social challenges, such as the lack of time for socializing with friends and family. As a result, the well-being of the students as well as their academic performance may be at risk.…”
Section: Perks and Setbacks Of A Working Studentmentioning
confidence: 99%